The Mother’s Role in Mother-Child Relationship Among Adolescents with Unwanted Pregnancies - Mohamed Faudzi, Noradila; Sumari, Melati; Mohamad Nor, Azmawaty; Abd Rahman, Norhafisah (‘Abqari Journal, 2021)
The mother’s role is essential in an adolescent’s development due to the challenges of life and exposure to the outside world, which affect and constantly change the mother’s role. This study intends to explore the experiences of the mother’s roles in the mother-child relationship among adolescents with unwanted pregnancies. A phenomenological approach was employed to obtain the essence of the experiences. A total of 10 participants comprising of five pregnant adolescents and their mothers were interviewed to understand the role played by the adolescents’ mothers during the pregnancy. A diary was distributed among the adolescents to allow them to externalise and express the experiences that they had with their mothers while being pregnant. This study used thematic analysis because it is flexible in interpreting the data and allows to approach large data sets more easily by sorting them into broad themes. Five themes emerged as follows: (a) supervising and monitoring, (b) rules and regulations, (c) showing affection, (d) educating adolescents, and (e) giving encouragement and support. This study provided insights on the mothers’ struggles in raising their adolescents which were highlighted from two perspectives: adolescents and mothers. The findings revealed the challenges faced by the mothers with various types of family structure.